PENINGKATAN KETERAMPILAN MENULIS SEDERHANA TERHADAP MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT BERBANTUAN PERMAINAN JEJAK KAKI KELAS I - Lisa Putri Wihana; Mohammad Kanzunnudin; M. Syaffruddin Kuryanto (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2024)
The aim of this research is to determine the improvement of simple writing skills in the Teams Games Tournament (TGT) model with the help of the Footprints game in class I students at SD 2 Demaan. Using a quantitative approach with a quantitative research design, a one-group pretest-posttest design experiment. By using a saturated sampling method, this research included 26 class I students as the population. With a sample size equal to the population, namely 26 respondents. Tests, observation and documentation are the methods used to collect data in this research. The data analysis technique used in this research is the N-Gain Test. The N-Gain test obtained an average value of 0.5958, which is included in the medium category because it is in the range 0.30≤70. This shows that Ha was accepted and Ho was rejected. This is proven that the application of the Teams Games Tournament (TGT) learning model assisted by the Footprints game resulted in an increase in the simple writing skills of class I students at SD 2 Demaan. Keywords: Teams Games Tournament (TGT), Footprint Games, Simple Writing Skills